New Theory and Old Canards about Family Violence Research. (31st July 2014) - Straus, Murray A.
Abstract : In response to three alternative viewpoints to his Presidential Address, "Discipline and Deviance: Physical Punishment of Children and Violence and Other Crime in Adulthood, " Straus clarifies several key points regarding the theorized connection between physical punishment and the etiology of violence. He draws on his extensive prior research to justify his conclusion that criticisms of his work on family violence are unfounded.